Acetyl-CoA synthetase 2 promotes acetate utilization and maintains cancer cell growth under metabolic stress - Schug, Zachary T; Peck, Barrie; Jones, Dylan T; Zhang, Qifeng; Grosskurth, Shaun; Alam, Israt S; Goodwin, Louise M; Smethurst, Elizabeth; Mason, Susan; Blyth, Karen; McGarry, Lynn; James, Daniel; et al. (Cancer cell, 2015)
A functional genomics study revealed that the activity of acetyl-CoA synthetase 2 (ACSS2) contributes to cancer cell growth under low-oxygen and lipid-depleted conditions. Comparative metabolomics and lipidomics demonstrated that acetate is used as a nutritional source by cancer cells in an ACSS2-dependent manner, and supplied a significant fraction of the carbon within the fatty acid and phospholipid pools. ACSS2 expression is upregulated under metabolically stressed conditions and ACSS2 silencing reduced the growth of tumor xenografts. ACSS2 exhibits copy-number gain in human breast tumors, and ACSS2 expression correlates with disease progression. These results signify a critical role for acetate consumption in the production of lipid biomass within the harsh tumor microenvironment.